PENGARUH RESIKO PEMBIAYAAN DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERBANKAN SYARIAH - Kurnia Rahmawati; Jeni Susyanti; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTFor two years beginning in the 2015-2016 period of profitability has fluctuated over the period. In the present study the authors will discuss on Funding and Liquidity Risk on profitability. The purpose of this study were (1) To determine the effect of risk financing partially on profitability in Islamic banking (2) To determine the effect of liquidity partially on profitability in Islamic banking (3) To determine the effect of financing risk and liquidity simultaneously on profitability in Islamic banking ,This study uses a type of replication development research, this study included Explanatory Research this study took samples from the population by using purposive sampling or judgment sampling method. By using two types of variables: Dependent variable (the dependent variable) and Independent Variables (independent variable). Results from this study is the result of Financing Risk variables significant effect on profitability, while liquidity result and no significant negative effect on profitability.Keywords: Effects of Risk Financing, Liquidity, Profitability